2018
DOI: 10.1155/2018/7519856
|View full text |Cite
|
Sign up to set email alerts
|

TLR3 Modulates the Response of NK Cells against Schistosoma japonicum

Abstract: Natural killer (NK) cells are classic innate immune cells that play roles in many types of infectious diseases. NK cells possess many kinds of TLRs that allow them to sense and respond to invading pathogens. Our previous study found that NK cells could modulate the immune response induced by Schistosoma japonicum (S. japonicum) in C57BL/6 mice. In the present study, the role of TLRs in the progress of S. japonicum infection was investigated. Results showed that the expression of TLR3 on NK cells increased sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
(44 reference statements)
1
9
1
Order By: Relevance
“…Signaling through MyD88 is crucial for host defense as the MyD88 pathway is vital not only for Toll-like receptors (TLRs), but is also required by the members of the interleukin-1 cytokine family, including IL-18 and IL-33 (82,83). Although, the expression of several TLRs on murine NK cells has been suggested, their roles in viral infection have not been clearly demonstrated (84). However, mice deficient in MyD88 have NK cells with defective IFN-g production and are susceptible to infections (46,85,86).…”
Section: Discussionmentioning
confidence: 99%
“…Signaling through MyD88 is crucial for host defense as the MyD88 pathway is vital not only for Toll-like receptors (TLRs), but is also required by the members of the interleukin-1 cytokine family, including IL-18 and IL-33 (82,83). Although, the expression of several TLRs on murine NK cells has been suggested, their roles in viral infection have not been clearly demonstrated (84). However, mice deficient in MyD88 have NK cells with defective IFN-g production and are susceptible to infections (46,85,86).…”
Section: Discussionmentioning
confidence: 99%
“…Poly I:C attenuates liver fibrosis in vivo partly through enhancing TLR3-induced NK cell cytotoxicity (27,28), selectively killing activated HSCs (17). Poly I:C, as a TLR3 agonist, has been shown to have multiple biological functions in various liver diseases such as HCV infection (29), HBV infection (30), and liver cancer (31), as well as in the hepatocarcinogenesis process (32).…”
Section: Discussionmentioning
confidence: 99%
“…TLRs represent one of the most studied pattern recognition receptor (PRR) families (Harris et al 2006;Tartey and Takeuchi 2017). Qu demonstrated that TLR3 is the primary molecule which modulates the activation and function of NK cells during Schistosoma japonicum (S. japonicum) infection in mice (Qu et al 2018). The expression levels of TLR3 on different pulmonary lymphocytes were increased after S. japonicum infection (Chen et al 2019).…”
Section: Discussionmentioning
confidence: 99%